WEATHER TYPES AT SELECTED METEOROLOGICAL STATIONS IN SIBERIA - DOBROWOLSKA, KSENIA (Bulletin of Geography. Physical Geography Series, 2015)
This paper presents the structure of weather types at four Siberian synoptic stations: Ostrov Kotelnyj, Verkhoyansk, Oymyakon and Yakutsk. The analysis has been performed on the basis of data published in the Internet database of synoptic messages OGIMET for the period of December 1999 to November 2013. Types of weather were determined based on the modified classification of weather types by Ferdynus (1997, 2004, 2013). The occurrence of particular groups, classes, and types of weather, and sequences of days with predominant weather types was identified. During the research period the structure of the weather types at the selected stations is characterized by a large number of observed types of weather, with the majority of them occurring with a low frequency. Frosty weather was predominant. The most frequently reported was the weather marked with numerical code 1100 (extremely frosty, clear without precipitation and calm) in Verkhoyansk (12.5%), 1300 (extremely frosty, cloudy without precipitation and calm) in Yakutsk (12.2%), 1200 (extremely frosty, partly clouded without precipitation and calm) in Oymyakon (11.6%) and 2201 (exceptionally frosty, partly clouded without precipitation and light breeze) in Ostrov Kotelnyj (6.7%).